ORIENTASI PASAR DAN ORIENTASI KEWIRAUSAHAAN DALAM MEMPENGARUHI KINERJA PEMASARAN DI MASA RECOVERY PANDEMI COVID-19 - Indah Yuni Astuti; Miftahul Munir (Journal of Management Small and Medium Enterprises (SMEs), 2022)
The COVID-19 pandemic has become a separate obstacle for society in general, ranging from social constraints to improving the economy of a society in particular. This situation must be taken into consideration by the household craft industry players to be able to survive and develop their business activities in generating productivity and profits through market orientation and entrepreneurship strategies. The purpose of this study was to determine the effect of market orientation and entrepreneurship on the marketing performance of the wood craft industry business actors in the village area of ​​Boro Kedungwaru, Tulungagung. The population and samples that became the object of this study were all wood craft business actor as many as 45 respondents. Sampling using saturated sampling technique, and data collection using a questionnaire with a Likert scale as the instrument. Data analysis used validity and reliability test, multiple linear regression test, determinant coefficient test and hypothesis testing (t test & F test). The results of the research conducted showed that 1) It was a significant and partial influence between market orientation and entrepreneurial orientation on the marketing performance of household handicraft business actors during the recovery period of the COVID-19 pandemic. 2). Market orientation and entrepreneurial orientation have a positive and significant impact simultaneously on the marketing performance of household handicraft business actors during the recovery period of the COVID-19 pandemic. The results of this study indicate that market orientation and entrepreneurial orientation have urgency and contribution in supporting the marketing performance of wood handicraft business actors especially during the COVID-19 pandemic. Keywords: Market Orientation, Entrepreneurship Orientation, Marketing Performance